Providing finance for rural women - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Women and credit - the experience of providing financial services to rural women in developing countries by Monica Fong and Heli Perrett 1991 157pp ISBN 88 85955 02 9 Pbk price Lr.20.000 Finafrica, Via San Vigilio 10 20142 Milan ITALY